1988
DOI: 10.1152/jappl.1988.64.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body posture on respiratory impedance

Abstract: The effects of posture on the mechanics of the respiratory system are not well known, particularly in terms of total respiratory resistance. We have measured respiratory impedance (Zrs) by the forced random noise excitation technique in the sitting and the supine position in 24 healthy subjects. Spirometry and lung volumes (He-dilution technique) were also measured in both postures. The equivalent resistance (Rrs), compliance (Crs), and inertance (Irs) were also calculated by fitting each measured Zrs to a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
42
2
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 0 publications
14
42
2
2
Order By: Relevance
“…This is not the case for FRC. Whereas in normal subjects, FRC falls by 700 -800 ml on going from the seated to the supine position (3,21,32,33,35), in severely obese subjects our laboratory (33,35) and others (3,32) have shown that supine falls in FRC are much smaller and may even be absent. The difference in values of FRC, FRC/TLC, and ERV between control and obese subjects shown in Table 2, therefore, would be even larger if the subjects were seated.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…This is not the case for FRC. Whereas in normal subjects, FRC falls by 700 -800 ml on going from the seated to the supine position (3,21,32,33,35), in severely obese subjects our laboratory (33,35) and others (3,32) have shown that supine falls in FRC are much smaller and may even be absent. The difference in values of FRC, FRC/TLC, and ERV between control and obese subjects shown in Table 2, therefore, would be even larger if the subjects were seated.…”
Section: Methodsmentioning
confidence: 54%
“…There is no consistent supine change in RV, but supine values of TLC and VC in normal subjects are, on average, slightly lower (200 ml or less) than seated values (3,21,32,33,35), with the reduction being attributed to an increase in central blood volume when supine. Similar small reductions in supine TLC and VC have been shown in obese subjects (3,32,33,35); indeed, previously our laboratory found that supine TLC in obese subjects, some of whom had lung restriction, was, on average, only 80 ml smaller than seated values (33).…”
Section: Methodsmentioning
confidence: 83%
“…Total resistance and reactance of the respiratory system were measured using the forced oscillation technique, as described in detail previously [11,13]. The forced oscillations (2 hPa peak-to-peak, 4-32 Hz) were generated by means of a loudspeaker enclosed in a chamber, servocontrolled [14] to withstand the pressure variation due to the subject's breathing, and applied at the mouth of the subject through the four-port valve ( fig.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 For patients experiencing orthopnoea, total lung capacity and vital capacity are enhanced with an elevated position. 4,5 Specifically in patients with HNC, the additional factor of excessive salivation is one of the most common patient-reported symptoms. An elevated position decreases pooling of accumulated saliva in the pharynx, reduces the hazard of choking and assists in fluid clearance.…”
Section: Introductionmentioning
confidence: 99%